Determination of Factors Affecting the Latent Period of Periviable Premature Rupture of Membranes: Cases and Evaluation of Newborn Outcomes - Kantarcı, Sercan; Karabulut, Alaattin; Bulut, Sertaç; Bölükbaşı, Mehmet; Kaygun, Bilgesu Çetinel; Ekin, Atalay (Journal of Fetal Medicine, 2025)
This study aimed to determine factors influencing the latent period in pregnant women with periviable preterm premature rupture of membranes (PPROM) between 22 and 26 weeks of gestation.A retrospective analysis of 106 pregnant women who delivered at our hospital between 2017 and 2021 was conducted. Diagnosis was confirmed using sterile speculum examination or the AmniSure test. Standard treatment included antibiotics, steroids, and tocolytic therapy. Maternal and fetal data, including C-reactive protein (CRP) levels, hemogram parameters, birth weight, and APGAR (Appearance, Pulse, Grimace, Activity, and Respiration) scores, were collected from medical records.A statistically significant difference was observed between CRP levels and the latent period. Patients with negative CRP values (< 5 mg/L) had a longer latent period (18.9 ± 17.05 days) compared with those with positive CRP values (> 5 mg/L, 8.47 ± 17.07 days). Chorioamnionitis was detected in 8 of 31 newborns, with a significant association between chorioamnionitis and necrotizing enterocolitis (NEC) (p = 0.043).PPROM poses significant maternal and neonatal risks, with the latent period directly impacting outcomes. Elevated CRP levels at admission were linked to shorter latency (p < 0.05), while tocolytic therapy prolonged latency without improving neonatal outcomes. The association between chorioamnionitis and NEC (p = 0.043) highlights the importance of early identification and management of risk factors. Individualized treatment with tocolytics, antibiotics, and corticosteroids is essential to optimize maternal and neonatal outcomes.
Keywords: preterm premature rupture of membranes; latent period; chorioamnionitis; respiratory distress syndrome